2010
DOI: 10.1038/sj.bjc.6605530
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α/NF-κB/Snail pathway in cancer cell migration and invasion

Abstract: Tumour necrosis factor-alpha (TNF-a) is an important inflammatory factor that acts as a master switch in establishing an intricate link between inflammation and cancer. A wide variety of evidence has pointed to a critical role of TNF-a in tumour proliferation, migration, invasion and angiogenesis. The function of TNF-a as a key regulator of the tumour microenvironment is well recognised. We will emphasise the contribution of TNF-a and the nuclear factor-kB pathway on tumour cell invasion and metastasis. Unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
495
1
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 640 publications
(536 citation statements)
references
References 47 publications
20
495
1
6
Order By: Relevance
“…It was recently reported that Akt could up-regulate Snail expression and induce invasion [40,48] . In addition, TNF-α-induced cell migration and invasion were associated with NF-κB-mediated stabilization of Snail [3,6] . Because NF-κB may bind to the human Snail promoter causing increased Snail expression [19] , we tested whether the regulation of Snail expression might be involved in the TNF-α-mediated migration and invasion of PC3 cells.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It was recently reported that Akt could up-regulate Snail expression and induce invasion [40,48] . In addition, TNF-α-induced cell migration and invasion were associated with NF-κB-mediated stabilization of Snail [3,6] . Because NF-κB may bind to the human Snail promoter causing increased Snail expression [19] , we tested whether the regulation of Snail expression might be involved in the TNF-α-mediated migration and invasion of PC3 cells.…”
Section: Discussionmentioning
confidence: 96%
“…Some crosstalk between pathways that are activated by TNF-α, such as NF-κB and PI3K/Akt [3,4] , is correlated with TNF-α-mediated tumor cell migration and invasion. For example, sustained activation of NF-kB by TNF-α has been reported to be involved in the regulation of tumor cell invasion via up-regulated expression of macrophage migration inhibitory factor (MIF), enhanced matrix metalloproteinases (MMPs) production and stabilized Snail [5,6] .…”
Section: Introductionmentioning
confidence: 99%
“…In the tumor microenvironment, it promotes migration and invasion. 25 Together with other inflammatory cytokines, TNF-α recruits additional inflammatory cells to the tumor microenvironment that may enhance proliferation and survival of mutated tumor cells. 25 As well as acting as an autocrine growth factor, TNF-α induces other growth factors including epidermal growth factor receptor and transforming growth factor (TGF)-β, resulting in further tumor proliferation.…”
Section: Bioactive Lipidsmentioning
confidence: 99%
“…25 Together with other inflammatory cytokines, TNF-α recruits additional inflammatory cells to the tumor microenvironment that may enhance proliferation and survival of mutated tumor cells. 25 As well as acting as an autocrine growth factor, TNF-α induces other growth factors including epidermal growth factor receptor and transforming growth factor (TGF)-β, resulting in further tumor proliferation. 25 IL-1β is also involved in cancer-related inflammation, 26 where it promotes angiogenesis and favors a prometastatic environment.…”
Section: Bioactive Lipidsmentioning
confidence: 99%
See 1 more Smart Citation